Duration of dual antiplatelet therapy (DAPT): a call for personalized medicine - Tahir, Usman; Yeh, Robert W. (Journal of Thoracic Disease, 2016)
Advances in drug-eluting stent (DES) technology have led to a decrease in the risk of developing stent thrombosis (1). Nevertheless, the optimal duration of dual antiplatelet therapy (DAPT) required after DES placement has remained elusive. Data from randomized studies have had conflicting results, with some suggesting that durations of DAPT as short as 3 or 6 months might be as effective in limiting these events as compared with longer durations previously supported by guidelines (2-5). On the other hand, the largest randomized study comparing DAPT durations, the DAPT study, found that continuation of therapy for 30 months significantly reduce rates of stent thrombosis and myocardial infarction (6), including among patients receiving second generation DES, at the expense of increased bleeding (7).